Evaluasi Sasaran Kinerja Pegawai (SKP) Pada Dinas Pertanian Dan Ketahanan Pangan Provinsi Jawa Timur - Kartika Dwi Aprilia; Tri Prasetijowati; Susi Ratnawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
The evaluation of employees’ performance, specifically government employees, gives 2 (two) sides of benefit, namely both for the employees’ performance themselves and for the governmental instances where they work. The evaluation of Employees’ Performance Targets (EPT) on government employees is a form of performance valuation based on The Government Regulation Number 30 of Year 2019 about Performance Valuation which aims to ensure objectivity of guidance for government employees that is done based on the performance system and career system. This study uses the descriptive method along with qualitative approach. According to the study results, it is known that the implementation of EPT on government employees’ working performance focusing on quantity, quality, cost, and time valuation. The results of performance evaluation is also in good state, as indicated by the timely manner of performance reporting by the employees. The obstacling factors of EPT implementation are namely the uneven facilities and infrastructures, and the time-consuming coordination between related institutions. Evaluation of EPT on government employees performance has 3 points of view, namely evaluators, performance, and indicators, and is done periodically. Decision making on human resource management also is in good state, as indicated by obstacles where some employees has their performance level evaluated as below expectation. This study suggests that leaders should be closer to their employees in order to intensify their guidance for their omployees on implementing the EPT, as well asgrowing the sense of bounding with their employees. Therefore, the implementation of employees’ performance evaluation would not be mere formality.